We believe in the Holy Spirit - Westhuizen, Henco van der; Ward, Graham (Cascade Books, 2023)
"We believe in the Holy Spirit is a collection of articles reflecting some of the most important ideas in pneumatology in recent years. Although the articles were not written to fit the articles of the Nicene Creed (381), linking these articles to the articles of the creed sheds imaginative light on the development of ideas in theologies of the Spirit." --
Nine of the contributions were previously published; see "Permissions", page [v]
"As the editor...I decdied to arrange the articles in the framework of the Nicene Creed (381). The articles however, were not written for this framework. ... The decision to arrange the articles in this way only came after the diverse articles were collected." -- Introduction, page xxv
Includes bibliographical references (pages 231-252)
Keywords: Nicene Creed; Symbole de Nicée; Aufsatzsammlung